Correspondence from Eugene Stead regarding evolution of the Physician's Assistant concept at Duke University - 1970 - Stead, Eugene A. (1970)
Letters written by Dr. Eugene A. Stead, Jr. in 1970 answering a variety of questions about the physician's assistant concept. The letters are as follows:(1) Stead to Duffy dated April 23, 1970 commenting on a draft bill for licensure of physician's assistants in California. "Although my personal predisposition is against licensure because of needless rigidities it often introduces, I can certainly understand why this approach may be necessary in your particular situation." Stead points out several items that disturb him, i.e., trying to over-define scope of practice in various specialties and extra burden placed on the medical board to enforce scope of practices - "In North Carolina, we have been considering a regulatory scheme -- less onerous than those you propose"; (2) Stead's reply to Byers dated July 31, 1970 about press release by National Academy of Sciences. Dr. Stead states that the report by the Board of Medicine "was designed as an attempt to cut through some of these inertial forces paralyzing the development of health manpower." Again, he pushes for the AMA and AAMC to determine standards for establishing schools and devise mechanism for accrediting them; (3) Stead's reply to Ricketts at AMA about an article stating long-range problems with PA concept. "Your authors have no sense of urgency. They don't know that, in spite of all the talk, very few persons are being educated. The AMA has not yet set up guidelines for the education of broadly trained assistants"; (4) Stead September 14, 1970 reply to Penfold stating he would welcome any publicity that the IZAAK Walton League of America could give to the PA concept because the "American Medical Association has not approved this new type of health worker -- the Federal government is supporting only a few programs"; and (5) Stead's reply to Bowles (NC State Senator) asking for his help to move the AMA and Federal Government to support the PA concept. He encourages Bowles to support pending NC enabling legislation for PAs.